2010
DOI: 10.4236/health.2010.212206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between food polyamines and gross domestic product in association with longevity in Asian countries

Abstract: The relationship between gross domestic pro- duct (GDP) and dietary profile, with a focus on polyamine intake, was investigated in 35 Asian countries. Data on food supply, GDP, and health condition were collected from databases of the United Nations, the International Monetary Fund, and the World Health Organization, respectively. The amount of polyamine intake from food was estimated using polyamine concentrations listed in published sources. The amounts of putrescine, spermidine, spermine, and total polyamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…Recently, the polyamine spermidine has been identified as a potent and specific inducer of autophagy (Eisenberg et al, 2009; Madeo et al, 2010). Spermidine is a natural dietary compound found in high concentrations in Mediterranean and Asian diets (Binh, 2010; Soda et al, 2010). Supplementation with spermidine extends lifespan in yeast and flies by an autophagy-dependent mechanism and reduces oxidative stress (Eisenberg et al, 2009; Guo et al, 2011; Minois et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the polyamine spermidine has been identified as a potent and specific inducer of autophagy (Eisenberg et al, 2009; Madeo et al, 2010). Spermidine is a natural dietary compound found in high concentrations in Mediterranean and Asian diets (Binh, 2010; Soda et al, 2010). Supplementation with spermidine extends lifespan in yeast and flies by an autophagy-dependent mechanism and reduces oxidative stress (Eisenberg et al, 2009; Guo et al, 2011; Minois et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there was a significantly higher supply of total polyamines in higher GDP countries, and it was suggested that increased polyamine intake may have some role in the difference in the prevalence of diseases associated with socioeconomic disparity (Binh et al 2010b). Although the daily amount of polyamine availability from foods in Asian countries was considerably lower than that reported in European countries, GDP of Asian countries was also positively correlated with polyamine content per energy (Binh et al 2010a). Furthermore, increased life expectancy was also associated with greater polyamine content per energy in Asian countries.…”
Section: Polyamines Derived From Dietary Sourcesmentioning
confidence: 69%
“…The polyamine content of a large range of different foods has recently been reported by Binh et al (2010aBinh et al ( , 2010b and polyamine intake was correlated with gross domestic product (GDP) and longevity. In a study of 49 European and other Western countries, differences in www.intechopen.com dietary intake were detected according to GDP (Binh et al, 2010b).…”
Section: Polyamines Derived From Dietary Sourcesmentioning
confidence: 99%
See 2 more Smart Citations